Role of Sustainable Tourism in Preserving Cultural Heritage of Afghanistan: A Comprehensive Review - Stanikzai, Irfan Ullah; Seerat, Dr. Abdul Hameed; Humdard, Wasiq Ullah (Society & Sustainability, 2024)
This comprehensive review investigates the role of sustainable tourism in preserving Afghanistan’s cultural heritage, given its rich tapestry of traditions, historical sites, and archaeological treasures. The purpose of the study is to assess the potential of sustainable tourism practices to mitigate the challenges faced by Afghanistan’s cultural heritage due to decades of conflict and instability while promoting economic development and community engagement. The study employs a systematic analysis of existing literature, case studies, and best practices from around the world to evaluate the effectiveness and applicability of sustainable tourism approaches in the Afghan context. It examines the economic, social, and environmental dimensions of sustainable tourism and their impact on the preservation of cultural heritage. The findings reveal that sustainable tourism offers significant economic benefits for Afghanistan, including job creation, income generation, and economic diversification. Additionally, it has the potential to foster social and cultural impacts through cultural exchange, community pride, and the revitalization of traditional crafts and practices. Furthermore, sustainable tourism can address environmental considerations by promoting the sustainable management and protection of natural landscapes, archaeological sites, and cultural monuments. The implications of this study highlight the importance of implementing sustainable tourism practices to preserve Afghanistan’s cultural heritage. It provides valuable insights and practical examples from successful initiatives in other countries, offering recommendations for policymakers, tourism practitioners, and cultural heritage management stakeholders.